Turbulent action at a distance due to stellar feedback in magnetized clouds. (November 2018) - Offner, Stella; Liu, Yue
Abstract A fundamental property of molecular clouds is that they are turbulent1, but how this turbulence is generated and maintained is unknown. One possibility is that stars forming within the cloud regenerate turbulence via their outflows, winds and radiation ('feedback')2 . However, disentangling motions created by feedback from the initial cloud turbulence is challenging. Here, we confront the relationship between stellar feedback and turbulence by identifying and separating the local and global impact of stellar winds. We analyse magnetohydrodynamic simulations in which we track wind material as it interacts with the ambient cloud. By distinguishing between launched material, gas entrained by the wind and pristine gas we show energy is transferred away from the sources via magnetic waves excited by the expanding wind shells. This action at a distance enhances the fraction of stirring motion compared with compressing motion and produces a flatter velocity power spectrum. We conclude that stellar feedback accounts for significant energy transfer within molecular clouds—an impact enhanced by magnetic waves, which have previously been neglected by observations. Overall, stellar feedback can partially offset global turbulence dissipation. The mechanisms that sustain turbulence in a molecular cloud are not well understood. Using magnetohydrodynamic simulations, the effects of stellar winds on a cloud are studied, finding that energy can be efficiently transferred in magnetic waves generated by this stellar 'feedback'.